Theoretical Study of Intermolecular Hydrogen Bonding and Interaction in Ethylene Glycol-Water Mixtures - Li, Wenxiu; Zhang, Jianbin; Liu, Quansheng; An, Shengli (Asian Journal of Chemistry, 2014)
Aqueous solution of ethylene glycol (EG) were used in the SO2 absorption processes. Meanwhile, the various spectra suggested that aqueous solution of ethylene glycol can bond with SO2 by the mean of hydrogen bonding and interaction. It is therefore important to understand the interaction of ethylene glycol with H2O at the molecular level. In this work, the ground-state structure and energies of ethylene glycol, H2O, EG2-H2O and EG/H2O1-3 hydrogen bonded clusters were investigated using density functional theory (DFT). Calculated IR spectra, dipole moments and rotational constants for all optimum conformers at the same level are provided for comparison with the experiments. The binding energies (-De0) and the calculated harmonic vibrational frequencies for ethylene glycol and H2O are in good agreement with previous calculated and experimental results. The -De0 values for ethylene glycol + H2O shows that the addition of H2O can disrupt the original hydrogen bonds in ethylene glycol system and ethylene glycol can be easily solved in water.